Evolution of Plant HECT Ubiquitin Ligases - Marín, Ignacio (Public Library of Science, 2013)
HECT ubiquitin ligases are key components of the ubiquitin-proteasome system, which is present in all eukaryotes. In this study, the patterns of emergence of HECT genes in plants are described. Phylogenetic and structural data indicate that viridiplantae have six main HECT subfamilies, which arose before the split that separated green algae from the rest of plants. It is estimated that the common ancestor of all plants contained seven HECT genes. Contrary to what happened in animals, the number of HECT genes has been kept quite constant in all lineages, both in chlorophyta and streptophyta, although evolutionary recent duplications are found in some species. Several of the genes found in plants may have originated very early in eukaryotic evolution, given that they have clear similarities, both in sequence and structure, to animal genes. Finally, in Arabidopsis thaliana, we found significant correlations in the expression patterns of HECT genes and some ancient, broadly expressed genes that belong to a different ubiquitin ligase family, called RBR. These results are discussed in the context of the evolution of the gene families required for ubiquitination in plants.